Anti-Interleukin 17A Biologic Therapy Attempts on Livedoid Vasculopathy: A Report of Case Series - Qi F; Gao Y; Jin H (Dove Medical Press, 2024)
Fei Qi, Yimeng Gao, Hongzhong Jin Department of Dermatology, State Key Laboratory of Complex Severe and Rare Diseases, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, National Clinical Research Center for Dermatologic and Immunologic Diseases, Beijing, 100730, People's Republic of ChinaCorrespondence: Hongzhong Jin, Department of Dermatology, State Key Laboratory of Complex Severe and Rare Diseases and Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, National Clinical Research Center for Dermatologic and Immunologic Diseases, Beijing, 100730, People's Republic of China, Tel +86-10-69151500, Email jinhongzhong@263.netAbstract: The application of biologics such as anti-tumor necrosis factor (TNF) has shown great efficacy in livedoid vasculopathy (LV). However, new biological options need to be identified for those with a high tuberculosis reactivation risk. In this study, we evaluated the efficacy of anti-17A biologics for LV therapy. Two patients with LV who were irresponsive to traditional anticoagulation therapy were studied at the outpatient dermatology clinic of Peking Union Medical College Hospital. All patients received anti-17A biological therapy for at least two-four weeks. Both patients reported an exacerbation of the skin lesions, which might indicate that the IL-17 pathway plays a critical role in LV pathogenesis.Keywords: livedoid vasculopathy, biologic therapy, TNF-alpha, IL-17, atrophied blanched